2019
DOI: 10.1016/j.ijpam.2019.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric pneumonia

Abstract: BackgroundPediatric pneumonia is a significant cause of inpatient care in the United States. Significant resource utilization and the high cost of care necessitate careful evaluation, especially with continuously decreasing financial resources. Several studies have evaluated subsets and regional impact of these diagnoses, but only a few have evaluated these on a national level.MethodsThis retrospective analysis utilized the 2009–2012 HCUP KID Inpatient Dataset to evaluate the relationship between pneumonia dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…In the paediatric population globally, viral pneumonia remained more typical and concerned the first 2 years of a child's life. After that, bacterial aetiology dominated [22]. The current results revealed a tendency to the most frequent occurrence of viral cases in patients up to 4-years-old (81.8% of all viral cases); however, in total in this age group, unidentified aetiology dominated (54.7% of all incidents).…”
Section: Discussionsupporting
confidence: 45%
“…In the paediatric population globally, viral pneumonia remained more typical and concerned the first 2 years of a child's life. After that, bacterial aetiology dominated [22]. The current results revealed a tendency to the most frequent occurrence of viral cases in patients up to 4-years-old (81.8% of all viral cases); however, in total in this age group, unidentified aetiology dominated (54.7% of all incidents).…”
Section: Discussionsupporting
confidence: 45%
“…They found higher incidence rates in the South; more than half of the patients had Medicare, and care was more expensive in the West. 22 Further, there are similar mortality rates between large and small hospitals, and greater severity/morality could be related to socioeconomic status. 22 For different disease states, results are mixed on if hospital teaching status affects disease outcomes, 23 , 24 and such a connection has yet to be shown for pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“… 22 Further, there are similar mortality rates between large and small hospitals, and greater severity/morality could be related to socioeconomic status. 22 For different disease states, results are mixed on if hospital teaching status affects disease outcomes, 23 , 24 and such a connection has yet to be shown for pneumonia. Previous research on health outcomes from teaching vs. non-teaching hospitals has found that public safety-net hospitals, treating patients regardless of insurance, tend to have worse results, treat more severe patients, and can still be costly, possibly because of patient sociodemographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there were an estimated 138 million cases of pneumonia in children under age 5 in 2015 [ 2 ], with pneumonia accounting for an estimated 14% of all deaths in this age group [ 4 ]. Pneumonia also contributes to high healthcare resource utilization [ 3 , 5 ], with approximately half of children under age 5 years with severe community-acquired pneumonia in developing countries requiring hospitalization [ 2 ]. However, the incidence varies widely by geography, with higher rates in developing countries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%